Matching-Adjusted Indirect Comparison of the Efficacy at Week 32 of Tralokinumab and Dupilumab in the Treatment of Moderate-to-Severe Atopic Dermatitis - Tiago Torres; Anne Sohrt Petersen; Ulla Ivens; Albert Bosch Vilaro; John Stinson; José Manuel Carrascosa (Dermatology and Therapy)
Abstract Introduction Tralokinumab and dupilumab are biological agents licensed for the treatment of moderate-to-severe atopic dermatitis (AD) in adult patients who are candidates for systemic treatment. However, no head-to-head studies of their efficacy have been conducted. This study indirectly compared the efficacy of tralokinumab and dupilumab, both in combination with topical corticosteroids (TCS), at week 32. Methods An unanchored matching-adjusted indirect comparison was conducted using individual patient data (IPD) from the ECZTRA 3 tralokinumab trial and aggregate data from the LIBERTY AD CHRONOS dupilumab trial. IPD were selected by applying inclusion criteria from LIBERTY AD CHRONOS and weighting to match summary baseline characteristics—age, sex, race, body mass index, disease duration, Eczema Area and Severity Index (EASI), Investigator’s Global Assessment (IGA), Dermatology Life Quality Index (DLQI) and SCORing Atopic Dermatitis index—of patients treated with dupilumab. Week 32 outcomes of interest were 50%, 75% or 90% improvements in EASI (EASI-50, EASI-75 and EASI-90), IGA scores of 0 or 1 (IGA 0/1), ≥ 4-point improvement in worst daily pruritus numerical rating scale (NRS) score, and mean improvements in DLQI and the Patient Oriented Eczema Measure (POEM). Results After matching, tralokinumab and dupilumab, both in combination with TCS, showed similar efficacy across clinical response endpoints at week 32 (IGA 0/1, tralokinumab 49.9% vs dupilumab 39.3%; EASI-50, 78.9% vs 77.5%; EASI-75, 71.5% vs 71.9%; EASI-90, 53.3% vs 56.2%). The mean change from baseline in DLQI was statistically significantly larger in the matched tralokinumab plus TCS population than in the dupilumab plus TCS arm (− 12.1 vs − 10.4, p = 0.005). Changes in POEM and worst daily pruritus NRS were similar in the two groups. Conclusion The results of this analysis demonstrate that, in combination with TCS, tralokinumab and dupilumab have similar efficacy in the treatment of moderate-to-severe AD at 32 weeks of therapy.